The stability of international environmental coalitions with farsighted countries: Some theoretical observations - Giulio Ecchia; Marco Mariotti (Fondazione Eni Enrico Mattei (FEEM), 1997)
We study a three-country model of international environmental agreements where countries may choose either to limit their emissions or to behave noncooperatively. First, we provide a taxonomy of various kinds of strategic situations. Then, by applying some recently developed game-theoretic techniques, we show that if countries are "farsighted" then there is scope for self-enforcing cooperation in several such situations.
Keywords: 330; Umweltabkommen; Spieltheorie; Gefangenendilemma; Theorie